Biofungicidas para el control de moniliasis en el cultivo de Theobroma cacao l. Clon 575 en la ESPAM MFL. - Pérez Calderón, Ernesto Daniel (2017)
This work aimed to reduce the incidence of M. roreri in the clone of cacao EET 575 by applying the biofungicides Tricho D (Trichoderma harzianum) and Basubtil (Bacillus subtilis). The field trial was carried out in the clonal cacao garden belonging to the Polytechnic of Manabí, Ecuador. Four variants were established (T1, Tricho D, T2, Basubtil, T3, Tricho D. + Basubtil, T4, Witness) arranged in a Completely Random Design with 9 replicates. Eight applications of biofungicides were performed, with a frequency of 21 days, using a motor pump. In the experimental material we analyzed the variables degree of external severity of moniliasis in ears per plant at 120 and 180 days and the efficacy between treatments in relation to the control, where the analysis of variance did not show significant differences, demonstrating that these Biotechnologies had no potential impact on disease control under field conditions. However, in the T3 variant, the highest percentage of healthy fruits with 82.58% and 66.51% in the two evaluation periods was found to be the most effective compared to T1 and T2 with 42% In relation to the witness. It is concluded that the combined effect of the two biofungicides should be further evaluated under field conditions, modifying the doses and frequencies of application.